Will you still need me, will you still feed me? Old-age pensions in Iceland from a gender perspective - Rögnvaldsdóttir, Steinunn; Pétursdóttir, Gyða Margrét (Stjórnsýslustofnun, 2012)
Icelandic women have through the years earned less occupational and supplemental pensions and depended more than men do on the basic pension of social security. Although women’s labour market participation has increased, the gender pay gap, unpaid labour in homes, and women’s fewer working hours in paid labour results in the extension of the labour market gender discrimination into old age. The structure of Icelandic pension funds is fundamentally male biased because of its tight connection to employment, despite the absence of direct discrimination factors. The article provides an overview of implications for a more women friendly pension system; based on multi-national research; the analysis of the Icelandic pension system, and statistical information on older women and men’s economic situation in Iceland. Adequate basic pension, elimination of labour market gender discrimination, and males taking greater responsibility for care- and housework, are some of the key issues in creating a more gender equal pension system. Sharing of pensions between spouses, the responsibility of pension-funds and companies, and possibilities of care credit systems to promote gender equality are also discussed.